Systematic school based assessment for an improved cognitive achievement (2006)
This study examined the possibility of using systematic school based assessment as a tool for improving the student's cognitive achievement at the junior secondary school level in the high priority four core subjects of mathematics, english language, social studies and integrated sciences. Four schools in Okene local govenement of Kogi state of Nigeira constitute the sample. Two classes were slected from JSS2 of each school. There were four experimental and four control groups to cover the four core subjects used in the study. Pre-test post-test experimental and control groups design was used while guided teacher-made tests were employed to check the effect of treatments-SSBA on the students. It was found that in all four subjects there were improvements by studentsn who underwent the SSBA treatment. Based on this outcome, it was recommended that SSBA together with other teaching methods be used in schools on regular basis to improve student's cognitive achievement.